(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study was motivated by students’ low learning outcomes regarding fraction arithmetic operations. The research aimed to analyze the types and frequencies of student errors in solving problems based on Newman’s stages. A descriptive qualitative approach was employed, involving 28 students from class VIA as subjects. Data were collected via a written test consisting of 10 problem-solving essay questions. Error analysis was based on Newman’s five stages: reading, comprehension, transformation, process skills, and conclusion. The results revealed that errors in drawing conclusions were the most prevalent (150 occurrences), followed by errors in process skills (133), transformation (106), comprehension (97), and reading (78). These frequencies represent the total number of error occurrences across all student responses to the 10 questions, rather than the number of individual students who made errors. Errors in drawing conclusions were characterized by incorrect or unsimplified answers, while process skill errors were evident in incomplete working steps. Transformation errors involved mistakes with symbols and numbers; comprehension errors stemmed from an inability to identify relevant information in the problems; and reading errors involved misreading fractions. These findings indicate that the most dominant errors occurred during the final stages of problem-solving, highlighting the need to strengthen procedural skills and emphasize accuracy when verifying final results.